2020
DOI: 10.1167/tvst.9.4.16
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1 Knockout Mice as a Genetic Model of Open-Angle Glaucoma

Abstract: A leading cause of blindness worldwide, glaucoma is often caused by elevated intraocular pressure (IOP) due to impaired aqueous humor outflow from the anterior chamber through Schlemm's canal (SC) and the trabecular meshwork. Despite the large clinical burden, glaucoma research and drug development are hindered by a limited selection of preclinical models that accurately recapitulate human disease. Here, we propose that Angpt1 conditional knockout mice may provide one such model. Angiopoietin/TEK (ANGPT/TEK) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
(68 reference statements)
0
20
1
Order By: Relevance
“…Using neural crest-specific Wnt1 -cre, we have shown that deletion of Angpt1 in the uveal tract recapitulates the glaucoma phenotype of whole-body knockouts, confirming the TM origin of SC-regulating ANGPT1. In comparison to our previous studies in whole body inducible Angpt1 knockouts, neural-crest specific Angpt1 knockout mice showed slightly higher IOP at 10 weeks of age 56 ( Angpt1 ΔNC: Control: 11.5, mutant: 21.2, Δ9.7 mmHg; Angpt1 -whole body: Control: 15.4, mutant: 20.9, Δ5.5 mmHg), possibly due to strain differences or improved excision of TM Angpt1 in Angpt1 ΔNC mice.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Using neural crest-specific Wnt1 -cre, we have shown that deletion of Angpt1 in the uveal tract recapitulates the glaucoma phenotype of whole-body knockouts, confirming the TM origin of SC-regulating ANGPT1. In comparison to our previous studies in whole body inducible Angpt1 knockouts, neural-crest specific Angpt1 knockout mice showed slightly higher IOP at 10 weeks of age 56 ( Angpt1 ΔNC: Control: 11.5, mutant: 21.2, Δ9.7 mmHg; Angpt1 -whole body: Control: 15.4, mutant: 20.9, Δ5.5 mmHg), possibly due to strain differences or improved excision of TM Angpt1 in Angpt1 ΔNC mice.…”
Section: Discussioncontrasting
confidence: 89%
“…RGCs were quantified as previously described 56 . Briefly, enucleated eyes were immersion fixed (2% formaldehyde in phosphate-buffered saline, pH 7.5) before retinas were dissected and blocked (5% donkey serum, 2.5% BSA, 0.5% Triton X100 in Tris buffered saline pH 7.5, overnight at 4°).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, sTIE2 is capable of binding angiopoietins to prevent them from activating TIE2 signaling (29). Provided the increase expression of MMPs in NC-Foxc2 -/mice and the crucial role of ANGPT/TIE2 signaling in SC development (25)(26)(27)40), we hypothesized that increased MMP activity in the TM may mediate cleavage of TIE2 in SC endothelium, resulting in higher production of sTIE2, impairment of ANGPT/TIE2 signaling, and impaired SC morphogenesis. To investigate this mechanism, we collected conditioned media from cultured human dermal LECs (HDLECs) treated with either DMSO vehicle or the MMP inhibitor GM-6001 at dosages shown to inhibit sTIE2 shedding in cultured HUVECs (29) or impair tubulogenesis in three-dimensional culture assays (47).…”
Section: Single-cell Transcriptome Analysis Identifies Molecular Sign...mentioning
confidence: 99%
“…In contrast to the limbal and conjunctival lymphatics which originate from emergent lymphatic vessels on the nasal side of the developing eye, SC morphogenesis is initiated from the blood limbal and radial vascular plexuses during postnatal development (19,22). Several key lymphatic vascular signaling pathways directly regulate SC morphogenesis and maintenance, such as vascular endothelial growth factor (VEGF)-C/ VEGF receptor (VEGFR)-3 (18), PROX1 (20), and angiopoietin (ANGPT)/TIE2 (21,(23)(24)(25)(26). Of clinical importance, TIE2 mutations have been previously identified in a subset of patients with PCG (23).…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was demonstrated that the integrity and functionality of SC is maintained by the signaling between angiopoietin 1 (Angpt-1) and its tyrosine kinase receptor Tie [9]. Reduction or even inactivation of the Angpt-1/Tie2 signaling during adulthood in duces SC degeneration and is a key factor for IOP disbalance [4,9,10]. Restoring this path way by adding recombinant Angpt-1 as a therapeutic agent is not straightforward becaus Angpt-1 is prone to aggregation and is therefore not suitable as a therapeutic agent [11] Recently, an Angpt-1 mimetic peptide sequence (HHHRHSF) was discovered [12][13][14].…”
Section: Introductionmentioning
confidence: 99%